An assessment of new regionalism: the case of Turkey - Türker, Kaner Atakan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
This study analyzes the New Regionalism literature, and evaluates the renewed planning agenda which is assigned for sub-national regions in Turkey by making use of the New Regionalism. For that purpose, initially, the history of regional development planning following the establishment of the Republic of Turkey in 1923 is discussed. Later, New Regionalism is examined, starting with an evaluation of its origins. The main concepts of the literature are introduced, and the severe criticisms raised against it are studied in depth. Today, New Regionalism provides the dominant discourse in regional studies, and contributes drastically to the regional planning agendas of international institutions. The European Union, which has a significant impact on Turkey’s political and economic issues, is one of these institutions. Therefore, after the intensified relations with the European Union following the Helsinki Summit, it was inevitable that the literature would penetrate into Turkey’s regional development strategies. This thesis searches for exactly these specific regional development strategies which can be grouped under the diffusion of New Regionalism. To this end, some public plans and documents, which are prepared by the State Planning Organization, Small and Medium Enterprises Development Organization, and Ministry of Industry and Trade in the last decade, are covered. The conclusion reached is that, as they are addressed by a step by step evaluation of these plans, most of them are heavily characterized by the New Regionalism literature. This study paves the way for possible future research which will seek to reformulate Turkey’s New Regionalist policies, by taking account of the criticisms.
Keywords: Regionalism -- Turkey.